Philosophy Behind Bars: Growth and Development in Prison - Szifris, Kirstine (Bristol University Press, 2021)
Male prisons can be dangerous places with a climate of distrust, but can long-term prisoners be given the space to reflect and grow ? This ground-breaking study found that engaging prisoners in philosophy education enabled them to think about some of the 'big' questions in life and as a result to see themselves and others differently.